Analisis Strategi Pengembangan Objek Wisata Hutan Mangrove Mirda Di Likupang, Kabupaten Minahasa Utara Sebagai Kawasan Strategis Pariwisata Nasional - Sony Wijanarko; Michelin Rompah (Jurnal Syntax Admiration, 2024)
Tourism has a strategic position in increasing the country's foreign exchange, therefore it can trigger economic growth, especially it can encourage in various countries to develop the tourism sector. This research aims to analyze the development strategies for the Mangrove Forest Mirda as Tourist Attraction in Likupang, North Minahasa Regency. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation. The results show that Mangrove Forest Mirda has great potential as  a tourist attraction, but there are several  weaknesses that need to be addressed , such as inadequate infrastructure, suboptimal management, and lack of community awareness about cleanliness and environmental  conservation.  Recommended development strategies include: leveraging strengths such as the colorful bridge and the vast mangrove forest, addressing weaknesses by improving infrastructure and enhancing management, exploiting opportunities through promotion and tourist activities, and countering threats by strengthening security and maintaining cleanliness and environmental sustainability.